Laboratory assessment of vitamin K status. Issue 2 (20th December 2019) - Card, David John; Gorska, Renata; Harrington, Dominic Jon
Abstract : Vitamin K is required for the ɣ-carboxylation of specific glutamic acid residues within the Gla domain of the 17 vitamin K-dependent proteins (VKDPs). The timely detection and correction of vitamin K deficiency can protect against bleeding. Vitamin K also plays a role in bone metabolism and vascular calcification. Patients at increased risk of vitamin K deficiency include those with a restricted diet or malnutrition, lipid malabsorption, cancer, renal disease, neonates and the elderly. Coagulation assays such as the prothrombin time have been used erroneously as indicators of vitamin K status, lacking sufficient sensitivity and specificity for this application. The measurement of phylloquinone (K1 ) in serum is the most commonly used marker of vitamin K status and reflects abundance of the vitamin. Concentrations <0.15 µg/L are indicative of deficiency. Disadvantages of this approach include exclusion of the other vitamin K homologues and interference from recent dietary intake. The cellular utilisation of vitamin K is determined through measurement of the prevalence of undercarboxylated VKDPs. Most commonly, undercarboxylated prothrombin (Protein Induced by Vitamin K Absence/antagonism, PIVKA-II) is used (reference range 17.4–50.9 mAU/mL (Abbott Architect), providing a retrospective indicator of hepatic vitamin K status. Current clinical applications of PIVKA-II include supporting the diagnosis of vitamin K deficiency bleeding of the newborn, monitoring exposure to vitamin K antagonists, and when used in combination with α-fetoprotein, as a diagnostic marker of hepatocellular carcinoma. Using K1 and PIVKA-II in tandem is an approach that can be used successfully for many patient cohorts, providing insight into both abundance and utilisation of the vitamin.